2005
DOI: 10.1242/dev.02030
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF promotes epithelial cell migration in eyelid development

Abstract: Heparin-binding EGF-like growth factor (HB-EGF) is a member of the EGF family of growth factors that binds to and activates the EGF receptor (EGFR)and ERBB4. Here, we show that HB-EGF-EGFR signaling is involved in eyelid development. HB-EGF expression is restricted to the tip of the leading edge of the migrating epithelium during eyelid closure in late gestation mouse embryos. Both HB-EGF null (HBdel/del) and secretion-deficient(HBuc/uc) mutant embryos exhibited delayed eyelid closure, owing to slower leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 46 publications
2
95
1
Order By: Relevance
“…Using an in vivo assay we have shown that Scribble is essential for proper wound healing in the mouse embryo, likely through the regulation of directed epithelial cell migration. Consistent with this idea, the circletail mouse (a second Scribble mutant mouse) exhibits an eye open at birth phenotype, which is commonly associated with disruptions to known cell migration regulators such as epidermal growth factor receptor (EGFR) and c-Jun (Berkowitz et al, 1996;Zenz et al, 2003;Mine et al, 2005). Thus, both in vitro and in vivo data presented here supports a critical role for Scribble in regulating directed migration in mammalian epithelium.…”
Section: Regulation Of Directional Migration By Mammalian Scribblesupporting
confidence: 79%
“…Using an in vivo assay we have shown that Scribble is essential for proper wound healing in the mouse embryo, likely through the regulation of directed epithelial cell migration. Consistent with this idea, the circletail mouse (a second Scribble mutant mouse) exhibits an eye open at birth phenotype, which is commonly associated with disruptions to known cell migration regulators such as epidermal growth factor receptor (EGFR) and c-Jun (Berkowitz et al, 1996;Zenz et al, 2003;Mine et al, 2005). Thus, both in vitro and in vivo data presented here supports a critical role for Scribble in regulating directed migration in mammalian epithelium.…”
Section: Regulation Of Directional Migration By Mammalian Scribblesupporting
confidence: 79%
“…Besides MAP3K1, embryonic eyelid closure depends on signals derived from WNT, Sonic hedgehog, BMP/Activin, FGF and EGF (Luetteke et al, 1993;Mine et al, 2005;Gage et al, 2008;Huang et al, 2009). In addition, eyelid closure requires the participation of a number of intracellular signaling kinases, such as JNK, ROCK and CDH1, and nuclear transcription factors, such as c-Jun, Fra-2, FOXL2, SMAD and GRHL3 (McHenry et al, 1998;Li et al, 2003;Zenz et al, 2003;Zhang et al, 2003;Uda et al, 2004;Thumkeo et al, 2005;Takatori et al, 2008;Yu et al, 2008;Naoe et al, 2010).…”
Section: Map3k1 In Ocular Surface Developmentmentioning
confidence: 99%
“…(21) HB-EGF gene expression has been demonstrated in a variety of tissues, predominantly the lung, heart, brain and skeletal muscle. (22) HB-EGF participates in a variety of physiological and pathological processes, (11) including wound healing, (23) eyelid formation, (24) blastocyst implantation, (25) retinoic acid-induced epidermal hyperplasia (26) and atherosclerosis. (27) Recently, HB-EGF knockout mice have been established.…”
Section: Structure and Physiological Functions Of Hb-egfmentioning
confidence: 99%